Estructura de la comunidad de peces arrecifales de Playa Mero, Parque Nacional Morrocoy, Venezuela - Rodríguez, José; Villamizar, Estrella (Revista de Biología Tropical, 2000)
The coral reef fish community was studied in Playa Mero, Morrocoy National Park, after the mass mortality of January, 1996 with a systematic sampling design. Transects and quadrates were used for corals, and a visual census for fishes. The coral community is highly disturbed with extensive areas of dead coral covered by algae, and low coverage and richness of coral species, gorgonians, sponges and briozooans. These factors have generated a relatively homogenius environment with respect to the fish community, which was dominated by Scaridae and Pomacentridae that represented 75% of fish. Dominant fishes were mainly herbivorous all fish) apparently because of the disturbance that caused the settling of algae.